THE EFFECT OF DELIGHTS ON CUSTOMER SATISFACTION, (AN APPLIED STUDY IN A SAMPLE OF PRIVATE BANKS ) - Prof. Dr. Hashim Nayef Hashim Al-Hachim (Scholar Express Journals, 2025)
The research aims to study the effect of delights on customer satisfaction through an applied study conducted on a sample of private banks.
Keywords: delights, Responsiveness, customer Satisfaction,Employee Competence:,Reliability.